Impact of a synthetic insecticide and plant extracts on Aphis craccivora (Hemiptera: Aphididae) and coccinellid species in common beans - Cardoso De Sousa, Mateus; Andaló, Vanessa; Zampiroli, Renan; Batista De Alvarenga, Cleyton; Aparecida De Assis, Gleice; Janoni Carvalho, Fábio; De Brito, Welington Adolfo; Silva De Faria, Lucas (Revista Colombiana de Entomología, 2021)
Bean crop is attacked by several phytophagous insects, affecting its production and causing losses to farmers. Among the insects considered as bean crop pests, aphids can cause economic damage by continuously sucking the plant sap throughout crop development. Thus, this study aimed to evaluate the control of Aphis craccivora on bean crop with insecticides and its effect on the presence of ladybugs. The tested products were: 1) imidacloprid + bifenthrin; 2) neem extract; 3) d-limonene, and, as a control treatment, water was applied. Insect mortality and the presence of ladybugs were checked every three days until harvest. There was a reduction in the population of aphids after the application of the products for up to 27 days. The presence of ladybugs was higher in the control treatment than in the treatments with insecticides. Thus, the tested products were considered potential in the control of A. craccivora. However, they also negatively affected the presence of coccinellids.